PENGEMBANGAN MEDIA PEMBELAJARAN TELINGGO (TELUR INTERAKTIF BOARD GAME) PADA MATA PELAJARAN MATEMATIKA - Puspita, Adelia; Amelia, Winda (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study was motivated by the low level of student engagement in learning at SDN Tebet Barat 08 South Jakarta, as teachers only used textbooks and rarely utilized interactive media. The study aims to develop the Telinggo (Interactive Egg Board game) learning medium for two-dimensional shapes, which is suitable for use based on the results of validity and effectiveness tests. The study employs a research and development method using the Borg and Gall model adapted by Sugiyono, limited to nine stages until the final product revision. The trial was conducted using a one-group pretest-posttest design. The results showed that the Telinggo media had very high validity, with 92% for media experts with very valid criteria, 91.6% for language experts with very valid criteria, and 98% for subject matter experts with very valid criteria. This media is effective in improving learning outcomes with a completion rate of 68% and an N-Gain value of 0.58, categorized as moderate. Therefore, Telinggo is suitable for use as a learning media for two-dimensional shapes in fourth-grade elementary school classrooms.